The Assessment of the Quality of Life in Visually Impaired People with Different Level of Physical Activity - Kamelska Anna Malwina; Mazurek Krzysztof (Sciendo, 2015)
Quality of life (QOL) is associated with factors such as health, physical functioning, life satisfaction, a sense of happiness, and others. In case of disabled people, much attention is paid to their QOL rather than only the improvement of physiological variables. In a group of blind and visually impaired people, the effect of physical activity (PA) on the socialization process, the ability to explore own personality traits, developing creativity, and more motivation and desire to overcome the difficulties associated with visual impairment were observed.